2021
DOI: 10.5198/jtlu.2021.1855
|View full text |Cite
|
Sign up to set email alerts
|

Spatial parameters for transportation: A multi-modal approach for modelling the urban spatial structure using deep learning and remote sensing

Abstract: A significant increase in global urban population affects the efficiency of urban transportation systems. Remarkable urban growth rates are observed in developing or newly industrialized countries where researchers, planners, and authorities face scarcity of relevant official data or geo-data. In this study, we explore remote sensing and open geo-data as alternative sources to generate missing data for transportation models in urban planning and research. We propose a multi-modal approach capable of assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 92 publications
3
6
0
Order By: Relevance
“…Another consideration is that there are significant differences in the errors based on the size, population density and land use of the spatial unit. This corresponds with previous studies that also found relationships between higher errors and lower percentages of residential land use and higher mixed or other land uses [11] and population density [21]. Therefore, the PLOS ONE physical configuration of an urban landscape affects the performance of the disaggregation methods.…”
Section: Plos Onesupporting
confidence: 89%
See 3 more Smart Citations
“…Another consideration is that there are significant differences in the errors based on the size, population density and land use of the spatial unit. This corresponds with previous studies that also found relationships between higher errors and lower percentages of residential land use and higher mixed or other land uses [11] and population density [21]. Therefore, the PLOS ONE physical configuration of an urban landscape affects the performance of the disaggregation methods.…”
Section: Plos Onesupporting
confidence: 89%
“…Therefore, when VHR data are available, the dasymetric method is found to be the best option: the accuracies are better, it takes less computational effort, and it is more straightforward and easier to apply. When land use data are available, the categorical dasymetric approach is found to provide the best results: accuracies improve considerable if the number of stories is available, confirming results of Stiller et al [11].…”
Section: Plos Onesupporting
confidence: 79%
See 2 more Smart Citations
“…Data on land-use for the identification of residential buildings can be substituted for other European countries with data from the European Urban Atlas (https://land.copernicus.eu/local/urban-atlas). For other countries, land-use data from the OpenStreetMap project have been successfully incorporated to assign land-use to buildings [63]. Another crucial data set for modeling of the energy demand, however, is the construction period of the building.…”
Section: Discussionmentioning
confidence: 99%